Kajian Kandungan Bahan Tambahan Pangan Berbahaya 2018– 2019 Se-Kota Pekalongan dan Implementasi Perda Kota Pekalongan Nomor 07 Tahun 2013 - Sujarwo Sujarwo; Rr. Vita Nur Latif; Ardiana Priharwanti (JURNAL LITBANG KOTA PEKALONGAN, 2020)
Supervision of food safety in Pekalongan City in 2010-2012 shows 6.27% of food contains hazardous food additives. Pekalongan City Government policies related to food safety are contained in Pekalongan City Regional Regulation Number 7 of 2013, but their implementation has not been studied. The research objective was to further identify types of food co ntaining dangerous hazardous food additives, to further identify the implementation of Pekalongan City Regulation No. 07 of 2013, and further identify the knowledge and attitudes of food producers in Pekalongan City. This research design is a combination of quantitative and qualitative studies. The results of the research further identified that the types of food that were most often found to contain hazardous food additives were dangerous for the types of preservatives (formalin and borax), namely meatball, indi and cilok types of food; yellow noodles; and terinasi (teri Medan); and otak-otak, while the dangerous hazardous food additives types of dye (Rhodamin B and Methanil Yellow) are Krupukuseg red colored; powdered seasoning; krupuk useg yellow colored; and pudding. Pekalongan City Regulation No.7 of 2013 concerning the Prohibition of the Use of Hazardous hazardous food additives, has been well implemented, but not optimal. Some of the knowledge and attitudes of producers in Pekalongan City already know about food safety. Keywords: Hazardous food additives, food safety, local regulations